Evaluation of the 3dMDface system as a tool for soft tissue analysis. (June 2017) - Hong, C.; Choi, K.; Kachroo, Y.; Kwon, T.; Nguyen, A.; McComb, R.; Moon, W.
Structured Abstract: Objectives: To evaluate the accuracy of three‐dimensional stereophotogrammetry by comparing values obtained from direct anthropometry and the 3dMDface system. To achieve a more comprehensive evaluation of the reliability of 3dMD, both linear and surface measurements were examined. Setting and Sample Population: UCLA Section of Orthodontics. Mannequin head as model for anthropometric measurements. Material and Methods: Image acquisition and analysis were carried out on a mannequin head using 16 anthropometric landmarks and 21 measured parameters for linear and surface distances. 3D images using 3dMDface system were made at 0, 1 and 24 hours; 1, 2, 3 and 4 weeks. Error magnitude statistics used include mean absolute difference, standard deviation of error, relative error magnitude and root mean square error. Intra‐observer agreement for all measurements was attained. Results: Overall mean errors were lower than 1.00 mm for both linear and surface parameter measurements, except in 5 of the 21 measurements. The three longest parameter distances showed increased variation compared to shorter distances. No systematic errors were observed for all performed paired t tests ( P <.05). Agreement values between two observers ranged from 0.91 to 0.99. Conclusions: Measurements on a mannequin confirmed the accuracy of all landmarks and parameters analysed in this study using the 3dMDface system. Results indicated that 3dMDface system is an accurate tool for linear and surface measurements, with potentially broad‐reaching applications in orthodontics, surgical treatment planning and treatment evaluation.